Formação continuada de educadoras infantis: uma proposta de intervenção - Silva, Cirlei Evangelista (2004)
The aims of the present study were to investigate the necessities of educators of small children during the course of their professional practice, propose an intervention model adequate to the researched institutional context and evaluate the referred model considering the impact for the training of the educator. For such a task, we worked with three educators from a community institution of Child Education. The work consisted of a training process which involved individual sessions, observations of their routine and training meetings. The process was discussed, focusing on the educators and the relations established during the study such as: analysis of aspects that interfere in the training process, the involvement of the educators- to-be and the different phases of the process, the relationship between the educators and the institution “Renascer”; the perception of the educators on the placement and collaboration of parents in the institutional work; the personal difficulties of the educators and the interference of these in their professional practice; interaction between educators and children during child-play and evaluation of the educators of the various moments of the research. The final analysis of the work permitted us to certify that our proposal seemed to have collaborated, during its twenty-four months duration, for quality changes in the service provided by the educators to the children. This fact was verified as it attended some necessities pointed out by the educators during the initial phase of the research such as play training, the making and organization of didactic-pedagogic material, the organization of the physical space and other themes.